Constructing Analogical Arguments in Solving Mathematical Problem: High School Students’ Interactions with ChatGPT - Gurit Wulan Jagadianti; Manuharawati; Wijayanti, Pradnyo (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
solving new problems. However, many students struggle to construct well-structured arguments when solving mathematical problems, they have encountered before. The use of artificial intelligence technology, such as ChatGPT, has emerged as a potential solution to support students in building analogical arguments. This study aims to describe high school students' analogical arguments in solving mathematical problems before and after interacting with ChatGPT. This research employed a descriptive qualitative approach. The participants consisted of two 10th-grade high school students who had studied trigonometry and had prior experience using ChatGPT. The participants were selected based on the completeness of the argument components they demonstrated. Data were collected through analogical argument tasks, semi-structured interviews, and interactions with ChatGPT. Data analysis referred to indicators of analogical arguments that integrate Toulmin’s argument components and Bartha’s analogical argument structure. The results showed that students' analogical arguments changed before and after interacting with ChatGPT. The structure of the analogical arguments became more organized after the interaction. ChatGPT helped students to reconstruct the arguments they had previously built. This study implies that the use of ChatGPT can be a potential alternative to assist students in developing analogical arguments when solving mathematical problems.